Graphic trauma and meaning in our online lives - Koenig, Alexa 1972-; Lampros, Andrea 1968- (Cambridge University Press, 2023)
What does research tell us about how to grapple with the onslaught of graphic and distressing imagery that floods our newsfeeds daily? This book is designed for professionals and everyday people, legislators and social media policymakers who are making sense of trauma and meaning in our online lives